2015
DOI: 10.1111/and.12472
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of polydatin on oxidative stress-mediated testicular damage by chronic arsenic exposure in rats

Abstract: Arsenic causes lipid peroxidation leading to alterations in antioxidant status in organisms. In this study, the reproductive effects of chronic exposure to arsenic and the protective effects of polydatin (PD) were evaluated in 35 Wistar male rats, which were divided equally into five groups. The control group received a normal diet and tap water, arsenic (100 mg l(-1) , approximately 1/50 of oral LD50 ) was given via drinking water to experimental groups except control group, and PD was orally given to the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 33 publications
(36 reference statements)
3
14
0
Order By: Relevance
“…The results of the present study indicated that the levels of phosphorylated AKT, JAK1 and STAT3 were markedly decreased following treatment of HCCML3 cells with polydatin; however, no change was observed in p38 and p-p38 expression. The protein p38 is involved in oxidative stress regulation, suggesting that polydatin may not increase intracellular reactive oxygen species, which is consistent with the findings of previous studies (38,39). FOXO1 belongs to the forkhead family and serves numerous roles, including cellular differentiation, proliferation, cell cycle progression, apoptosis and glucose metabolism (40).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study indicated that the levels of phosphorylated AKT, JAK1 and STAT3 were markedly decreased following treatment of HCCML3 cells with polydatin; however, no change was observed in p38 and p-p38 expression. The protein p38 is involved in oxidative stress regulation, suggesting that polydatin may not increase intracellular reactive oxygen species, which is consistent with the findings of previous studies (38,39). FOXO1 belongs to the forkhead family and serves numerous roles, including cellular differentiation, proliferation, cell cycle progression, apoptosis and glucose metabolism (40).…”
Section: Discussionsupporting
confidence: 92%
“…Further, reduced reproductive organ weights and the disorganization of testicular and cauda epididymal architecture could be attributed to the inadequate supply of androgens . We found a significant reduction in the activity levels of SOD [EC: 1.15.1.1], CAT [EC:1.11.1.6], and GSH levels with a concomitant increase in the LPx levels in the testis and the cauda epididymis of arsenic‐treated rats suggesting accumulation of superoxides and peroxides with altered glutathione system . Moreover, accumulation of protein carbonyls may suggest protein oxidation in the selected tissues of arsenic‐treated rats…”
Section: Discussionmentioning
confidence: 79%
“…Catalase is the most important cellular antioxidant. It can degrade O 2 and decompose H 2 O 2 and result in a decrease in oxidative stress, which is the effective way of protection from ROS attack ( Ince et al., 2014 ). Glutathione peroxidase is an enzyme involved in scavenging the ROS and protecting the body from LPO by reducing both lipidic and nonlipidic hydroperoxides as H 2 O 2 ( Avanzo et al., 2001 ).…”
Section: Discussionmentioning
confidence: 99%